Preserving data replication consistency through ROWA-MSTS - Ahmad, Noraziah; Sidek, Roslina; Klaib, Mohammad F. J.; Che Fauzi, Ainul Azila; Abd Wahab, Mohd Helmy; Wan Mohd, Wan Maseri (Springer, 2011)
In modern distributed systems, replication receives particular awareness to provide high data availability, reliability and enhance the performance of the system. Replication becomes as significant mechanism since it enables organizations to provide users with admission to current data where and when they need it. Integrated VSFTPD with Read-One-Write-All Monitoring Synchronization Transaction System (ROWA-MSTS) has been developed to monitor data replication and transaction performs in distributed system environment. This paper presents the ROWA-MSTS framework and process flow in order to preserve the data replication consistency. The implementation shows that ROWA-MSTS able to monitor the replicated data distribution while maintaining the data consistency over multiple sites.